Motivation and Regular Salary as Determinants of Agricultural Science Teacher’s Commitment and Accomplishment of their Professional Responsibilities in Rivers State, Nigeria - Emeya, Salome; Antiaobong, Ekong O. (European Scientific Journal, ESJ, 2016)
The study examined motivation and regular salary as determinants of agricultural science teachers’ commitment in Port Harcourt Local Government Area of Rivers State, Nigeria. Survey and correlational research designs were adopted. A sample size of 142 subjects was used in this study. This comprised of 96 Agricultural Science teachers in both junior and senior secondary schools in Port Harcourt, 12 Principals, 24 Vice Principals in both junior and senior secondary schools in Port Harcourt, and 10 Supervisors in Port Harcourt. The Teachers’ Motivation Inventory (TMI), Teachers’ Regular Salary Scale (TRESS), and Agricultural Science Teachers’ Commitment Questionnaire (ASTCQ) instruments were used. The instruments were validated by experts in Education and Agricultural Science. The reliability of the instruments was established using the Cronbach Alpha method to obtain indices of 951, .902, and .844 for the TMI, TRESS and ASTCQ instruments, respectively. Data obtained from the 129 copies of the TMI, TRESS, and ASTCQ instruments was analyzed using multiple linear regression analysis. The result revealed that motivation and regular payment of salary jointly contributes to Agricultural Science teachers’ commitment in Port Harcourt Local Government Area of Rivers State. Furthermore, government ensuring the teachers’ regular promotion, alongside providing teachers’ with incentives like bonuses, class attendance and practical allowances etc., were among the proffered recommendations. This was targeted at increasing Agricultural Science teachers’ level of commitment in secondary schools.